The roles of astrocytic phagocytosis in maintaining homeostasis of brains - Se Young Lee; Won-Suk Chung (Elsevier, 2021)
In the central nervous system, microglia are regarded as the main cells responsible for phagocytosis, contributing to neural circuit refinement and homeostasis through synapse elimination. However, recent findings have shown that astrocytes also actively participate in synapse homeostasis through phagocytosing synapses, neuronal debris, axonal mitochondria, and pathological protein aggregates. In addition, it has been also suggested that astrocytes may regulate microglial phagocytosis by secreting molecules such as IL-33 and C3. Here, we have introduced key findings regarding direct and indirect astrocyte-mediated phagocytosis in CNS development, the sleep/wake cycle, and aging. We have also discussed current information about reactive astrocytes and their phagocytic function in the diseased brain, focusing on ischemia and Alzheimer's disease. Through this review, we aim to provide an overview of the current status as well as future perspectives regarding the important role of astrocytic control of phagocytosis.